1995
DOI: 10.1111/j.1365-2222.1995.tb00395.x
|View full text |Cite
|
Sign up to set email alerts
|

Human auto‐anti‐idiotypic antibodies to mite‐specific IgE can degranulate human basophils in vitro

Abstract: These results indicate that spontaneously produced human anti-Ids can modulate the reactivity of human basophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…It has been suggested that they play a putative role in IgE synthesis regulation, via the IgE receptor (FcεRI or CD23) on B lymphocytes, or via inflammatory cells, like mast cells, eosinophils or neutrophils. 16–18 These autoantibodies also seem to have a regulatory influence on human IgE mRNA synthesis as well as interleukin‐4‐induced proliferation of human mononuclear cells. 24 However, to date, interactions between IgE antibodies and IgE autoantibodies in atopic patients are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that they play a putative role in IgE synthesis regulation, via the IgE receptor (FcεRI or CD23) on B lymphocytes, or via inflammatory cells, like mast cells, eosinophils or neutrophils. 16–18 These autoantibodies also seem to have a regulatory influence on human IgE mRNA synthesis as well as interleukin‐4‐induced proliferation of human mononuclear cells. 24 However, to date, interactions between IgE antibodies and IgE autoantibodies in atopic patients are not clear.…”
Section: Discussionmentioning
confidence: 99%
“…The capability of human anti-idiotypic IgG purified from mite allergic patients to recognize cell bound IgE idiotypes of other donors, and to induce mediator release of basophils in the absence of allergen was demonstrated 29. Consequently, the possibility that degranulation in response to anti-ids could be a general event in allergy was proposed.…”
Section: The Functional Role Of Anti-ids In Allergymentioning
confidence: 99%
“…Thus, the Dactylis pollen affinity chromatography allowed basophil-inhibitory antibodies to be isolated in the eluate and appears to have eliminated basophilstimulating antibodies in the flow-through. According to a recent report [30], at least part of the basophilstimulating antibodies recovered in the flow-through of the Dactylis pollen affinity-column must be autoantiidiotypic antibodies to grass pollen-specific Igl Precisely, we have shown that the flow-through very probably contained autoanti-idiotypic antibodies, that prevented some of the specific IgE from binding to the Dactylis pollen column (Batard et al. Allergy, in press).…”
Section: Discussionmentioning
confidence: 62%